Influence of ancient armies’ military arts on forms of combat order of the Interior Troops units - Varakuta, V. P.; Glazkov, О. V. (Honor and Law, 2019)
The influence of ancient armies’ military arts on the selection of forms of combat order, Troops of the Interior units, Ukraine, depending on the assigned combat-routine mission is shown and defined.